O curso de pedagogia e a universitarização do magistério no Brasil: das disputas pela formação docente à sua desprofissionalização - Sarti, Flavia Medeiros (Faculdade de Educação da Universidade de São Paulo, 2019)
Abstract This article focuses on the Brazilian process of raising the formation of teachers working at the first years of basic education to the level of higher education, problematizing their qualification as a classic case of universitarization and proposing a way of characterizing it that we deem to be more precise and proficuous for the debate about the relations between the formation and professionalisation of those teachers. Based on literature review, it explores the cultural dimension and the symbolic struggles mobilized in that process, so as to characterize it as a sui generis case of universitarization, largely conducted by non-university institutions, and implemented through an atypical movement of institutional transfer – to the Pedagogy course –, which did not take into account the pre-existing formative structures and did not absorb them, as is more commonly the case in processes of universitarization. The article concludes that such universitarization was marked by processes of autonomization and of deprofessionalisation of teachers’ education, particularly due to the sociocultural effacement imposed to the teaching profession. Contrary to the expectations that legitimized it in the educational field, such universitarization conducted through institutional transfer is shown to be incompatible with the objectives of professionalisation of the teaching profession, which prescribe, among other factors, the increase of the control exerted by teachers over the processes concerning their work, among which is included the task of educating the future generations of teachers.

Resumo Este artigo focaliza o processo brasileiro de elevação ao nível superior da formação dos professores que atuam nos anos iniciais da educação básica, problematizando sua qualificação como um caso clássico de universitarização, e propondo uma maneira de o caracterizar que, considera-se, seja mais precisa e prolífica para o debate sobre as relações entre a formação e a profissionalização desses professores. Fundamentando-se em revisão de literatura, explora a dimensão cultural e as lutas simbólicas mobilizadas em tal processo, de modo a caracterizá-lo como um caso sui generis de universitarização, levado a efeito em grande parte por instituições não universitárias e implementado por meio de um movimento atípico de transferência institucional – para o curso de pedagogia –, que não considerou as estruturas formativas pré-existentes e não as absorveu, como ocorre mais comumente nos processos de universitarização. Conclui que essa universitarização foi marcada por processos de autonomização e de desprofissionalização da formação docente, sobretudo devido ao apagamento sociocultural imposto ao magistério. Contrariando as expectativas que a legitimaram no campo educacional, essa universitarização realizada por transferência institucional mostra-se incompatível com os propósitos de profissionalização do magistério, o qual prevê, entre outros fatores, o aumento do controle que os professores exercem sobre os processos concernentes ao trabalho que realizam, entre os quais se encontra a tarefa de formar as próximas gerações docentes.
The pedagogy course and the universitarization of teaching in Brazil: from the disputes over teachers’ education to its deprofessionalisation
Keywords: Universitarization; Teacher professionalisation; Field of teacher education; Culture of the teaching profession; Universitarização; Profissionalização docente; Campo da formação docente; Cultura do magistério